Hubungan Bobot Telur Tetas Dengan Egg Weight Loss Dan Bobot Doc Ayam Hasil Persilangan Pejantan Sentul Dengan Induk Ayam Nunukan - Junaedi Junaedi; Husnaeni Husnaeni (Musamus Journal of Livestock Science, 2019)
purpose of this study is to determine the relationship between hatching egg weights with egg weight loss and DOC weights of Sentul male crosses with Nunukan broodstock. The tool used in this research is a unit of automatic digital hatching machine (temperature regulation and automatic turning). The research material was two male Sentul male chickens and four Nunukan mother chickens. The chicken is crossed and then the eggs are collected to be hatched eggs. The equipment used in this study is digital cameras, digital scales, calculators and stationery and table sheets for filling raw data. The coded eggs are put into the hatching machine for 21 days. The parameters measured in this study are; Hatching egg weight (Gram), egg weight Hatch day 18th, egg weight loss (%) / Egg shrinkage, DOC weight: DOC weight is measured by weighing the newly hatched chicks ie on days 21-22, the correlation value between weights hatching eggs with egg weight loss, the correlation value between hatching egg weight and DOC weighting. Data analysis using correlation. The results obtained are the average hatching egg weight of 45.13 ± 2.41 grams, the average hatching eggs on the 18th day 40.13 ± 2.18 grams, egg weight loss 11.08 ± 0.73%, DOC 34 weight, 04 ± 2.07 grams, correlation of hatching egg weight to DOC weight of 0.91, correlation of hatchingto egg weightegg weight loss -0.01. Based on the results of the study it can be concluded that the characteristics of Sentul crossbreed hatching eggs with Nunukan broodstock are in the normal range, correlation of hatching egg weight with very high DOC weight and positive correlation, correlation of hatchingwith egg weightegg weight loss lowand negative correlation.